Hyperforin, the major metabolite of St. John’s wort, exhibits pan-coronavirus antiviral activity - Raczkiewicz, Imelda; Rivière, Céline; Bouquet, Peggy; Desmarets, Lowiese; Tarricone, Audrey; Camuzet, Charline; François, Nathan; Lefèvre, Gabriel; Silva Angulo, Fabiola; Robil, Cyril; Trottein, François; Sahpaz, Sevser; et al. (Frontiers in Microbiology, 2024)
The COVID-19 pandemic caused by the SARS-CoV-2 virus has underscored the urgent necessity for the development of antiviral compounds that can effectively target coronaviruses. In this study, we present the first evidence of the antiviral efficacy of hyperforin, a major metabolite of St. John's wort, for which safety and bioavailability in humans have already been established. Antiviral assays were conducted in cell culture with four human coronaviruses: three of high virulence, SARS-CoV-2, SARS-CoV, and MERS-CoV, and one causing mild symptoms, HCoV-229E. The antiviral activity was also evaluated in human primary airway epithelial cells. To ascertain the viral step inhibited by hyperforin, time-of-addition assays were conducted. Subsequently, a combination assay of hyperforin with remdesivir was performed. The results demonstrated that hyperforin exhibited notable antiviral activity against the four tested human coronaviruses, with IC50 values spanning from 0.24 to 2.55 µM. Kinetic studies indicated that the observed activity occur at a post-entry step, potentially during replication. The antiviral efficacy of hyperforin was additionally corroborated in human primary airway epithelial cells. The results demonstrated a reduction in both intracellular and extracellular SARS-CoV-2 viral RNA, confirming that hyperforin targeted the replication step. Finally, an additive antiviral effect on SARS-CoV-2 was observed when hyperforin was combined with remdesivir. In conclusion, hyperforin has been identified as a novel pan-coronavirus inhibitor with activity in human primary airway epithelial cells, a preclinical model for coronaviruses. These findings collectively suggest that hyperforin has potential as a candidate antiviral agent against current and future human coronaviruses..